Dorsal Spine Giant Cell Tumor with paraplegia: A Case Report (Bangladesh Journal of Neuroscience, 2015)
Patients of Giant cell tumors (GCT) of the spine is rarely seen . We reported a case of GCT of the eleventh dorsal vertebra presented by severe backache with paraplegia in a 30 year old woman. Imaging showed an osteolytic lesion invading the vertebral body, the posterior arch and compression of the spinal cord. Neurological decompression was performed but pain recurred after 2 months. The MRI of spine revealed recurrence of tumor and again surgical decompressions was done along with long segment transpedicular fixation and patient was significantly improved. A surgical biopsy was obtained at the same time to confirm the diagnosis. Giant cell tumor is not so common in thoracic region. We believe that the gross removal of tumor provide good outcome for the patient.Bangladesh Journal of Neuroscience 2015; Vol. 31 (1): 45-49